THEME, RHEME AND THEMATIC PROGRESSION OF STUDENTS’ HORTATORY EXPOSITION TEXT AT THE TWELFTH GRADE OF MAN 2 MODEL MEDAN - Fajriah Hasanah; Anni Holila Pulungan; I Wy. Dirgeyasa (Universitas Negeri Medan, 2017)
This study deals with the theme, rheme and thematic progression of students’ hortatory exposition text of the Twelfth Grade at MAN 2 Model Medan. The objectives of the study were to investigate thematic progression pattern used and the misuse of theme and rheme occurs in students’ hortatory exposition text. This study was conducted by using descriptive qualitative method. The data in this study were clauses of students’ hortatory exposition text. The instrument for collecting data was writing test of hortatory exposition text. The data were analyzed by using interactive model technique of Miles, Huberman and Saldana (2014). The findings indicated that there were two patterns of thematic progression used in students’ hortatory exposition text, they were Theme Reiteration/Constant Theme Pattern (TR/CTP), and Zig-zag/Linear Theme Pattern (Zig-zag/LTP). In terms of the problems of the misuse from theme and rheme, there two occurred in the students’ hortatory exposition text, they were the problems of brand new theme and empty rheme. Keywords: Theme, Rheme, Thematic Progression, Hortatory Exposition text.